(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This empirical analysis investigates the relationship between effective knowledge management practices and organizational agility. Knowledge management, encompassing processes like knowledge creation, capture, storage, sharing, and application, has become increasingly crucial for organizations in dynamic and competitive environments